Performance Measures for Optimizing Diverging Interchanges and Outcome Assessment with Drone Video. Issue 1 (January 2015) - Hainen, Alexander M.; Stevens, Amanda L.; Day, Christopher M.; Li, Howell; Mackey, Jamie; Luker, Matt; Taylor, Mark; Sturdevant, James R.; Bullock, Darcy M.
Diverging diamond interchanges (DDIs) are an emerging interchange configuration that eliminates the need for left-turn phases in conventional diamonds and may be less expensive to construct than some alternative geometries. This paper examines signal timing for DDIs. DDI signal timing typically has used a two-phase configuration that reflects the two competing movements at the crossover points at each inter section of the DDI. This configuration inherently contains some inefficiency: (a) there is potential for internal queuing under two-phase configuration and (b) it is possible for the inflow demand to exceed outflow capacity of the interchange. This paper uses high-resolution event data to develop performance measures for evaluating operations at a DDI in Salt Lake City, Utah. Alternatives to the existing signal timing within the two-phase configuration are modeled and tested with a field deployment. The field deployment demonstrated the ability to prioritize ramp or through vehicles within the two-phase configuration. Additionally, a new three-phase configuration was developed and deployed to address the internal queuing that occurs with two-phase timing. With this new configuration, the flows from one DDI intersection to the other are balanced, and progression within the DDI is improved. With the implementation of the three-phase configuration, the percentage of vehicles arriving on green at the heaviest internal movement within the DDI increased from 53% to 92%. To illustrate these performance measures and improved DDI operation qualitatively, a video from a tethered unmanned aerial vehicle demonstrated the vehicle arrival characteristics by overlaying vehicle detection and signal state graphics on the video.